RNA Interference of Four Genes in Adult Bactrocera dorsalis by Feeding Their dsRNAs - Li, Xiaoxue; Zhang, Mingyan; Zhang, Hongyu (PloS one, 2011)
RNA interference (RNAi) is a powerful method to inhibit gene expression in a sequence specific manner. Recently silencing the target gene through feeding has been successfully carried out in many insect species. Escherichia coli strain HT115 was genetically engineered to express dsRNA targeting genes that encode ribosomal protein Rpl19, V type ATPase D subunit, the fatty acid elongase Noa and a small GTPase Rab11. qRT-PCR showed that mRNA level of four target genes was reduced compared to ds-egfp control by feeding either engineered bacteria or dsRNAs. The maximum down-regulation of each gene varied from 35% to 100%. Tissue specific examination indicated that RNAi could be observed not only in midgut but also in other tissues like the ovary, nervous system and fat body. Silencing of rab11 through ingestion of dsRNA killed 20% of adult flies. Egg production was affected through feeding ds-noa and ds-rab11 compared to ds-egfp group. Adult flies were continuously fed with dsRNA and bacteria expressing dsRNA for 14 days and up-regulations of target genes were observed during this process. The transcripts of noa showed up-regulation compared to ds-egfp control group in four tissues on day 7 after continuous feeding either dsRNA or engineered bacteria. The maximum over-expression is 21 times compared to ds-egfp control group. Up-regulation of rab11 mRNA level could be observed in testes on day 7 after continuous bacteria treatment and in midgut on day 2 after ds-rab11 treatment. This phenomenon could also be observed in rpl19 groups. Our results suggested that it is feasible to silence genes by feeding dsRNA and bacteria expressing dsRNA in Bactrocera dorsalis. Additionally the over-expression of the target gene after continuously feeding dsRNA or bacteria was observed.